A new species of Dipsas (Squamata: Colubridae) from Guyana - MacCulloch, Ross D (2004)
A new species of Dipsas is described from the Pakaraima Mountains of Guyana. The new species is characterised by 15 dorsal scale rows with the middorsal row slightly enlarged, four pairs of chinshields with the first pair elongate, elongate loreal entering orbit, one preocular, six upper labials, and head narrow anteriorly, increasing in width posteriorly. It could not be determined to which of Peters’ (1960) species groups the new species belongs. The new species is known only from 1490 m elevation on Mount Ayanganna, a tepui in the Guiana Shield, where it was found in high-tepui low-canopy habitat, in bromeliads or branches. This is the first record of Dipsas as a member of the Guiana Shield high-tepui herpetofauna.